How uncertainty and ambiguity in tournaments affect gender differences in competitive behavior - Loukas Balafoutas; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2019)
Tournament incentives prevail in labor markets. Yet, the number of tournament winners is often unclear to competitors. While it is hard to measure how this uncertainty affects work performance and willingness to compete in the field, it can be studied in a controlled lab experiment. We present a novel experiment where subjects can compete against each other, but the number of winners is either uncertain (but with known probabilities) or ambiguous (with unknown probabilities for different numbers of winners). We compare these two conditions to a control treatment with a known number of winners. We find that ambiguity induces a significant increase in the performance of men who choose to compete, while we observe no change for women. Men also increase their willingness to enter competition in the presence of ambiguity. Overall, both effects contribute to men winning the tournament significantly more often than women under uncertainty and ambiguity. These findings suggest that management should make tournament conditions transparent and information available in order to prevent gender disparities from increasing under uncertainty and ambiguity.
Keywords: C91; D03; D09; 330; Gender; competition; uncertainty; ambiguity; experiment